Clothing consumption: analysis of fast fashion and slow fashion consumer motivations (Revista de Ensino em Artes, Moda e Design, 2023)
In the fashion industry, from fabric production to product disposal by the final consumer, there is environmental pollution. The wide variety of products, rapid trends and exaggerated consumption generate a great environmental impact. However, with the advancement of technology present in the Fourth Industrial Revolution, changes are taking place in the profile of consumers as they have more and more information about production processes and are aware of socio-environmental wear and tear. The aim of this study is to present the characteristics and profile of two types of fashion consumers: those who consume from slow fashion companies and those who opt for fast fashion companies, and to encourage sustainable consumption. To support the development of this research, a bibliographic survey will be carried out that will indicate characteristics of consumer behavior and the consumption of the fashion product. To complement the study, exploratory quantitative research will be carried out to know the profile of consumers and understand the motivations for consumption. With the development of the research, it is expected to understand the consumption motivations and, in this way, propose actions to motivate the sustainable consumption.
Keywords: consumption; fashion; sustainability